The Role of Chlamydia trachomatis in Male Infertility - Jaramillo-Rangel, Gilberto; Gallegos-Avila, Guadalupe; Ramos-Gonzalez, Benito; Alvarez-Cuevas, Salomon; Morales-García, Andres M.; Sanchez, Jose Javier; Miranda-Maldonado, Ivett C.; Niderhauser-Garcia, Alberto; Ancer-Rodriguez, Jesus; Ortega-Martinez, Marta (IntechOpen, 2012)
None